EFFECT OF EXCHANGE RATES AND INTEREST RATES ON STOCK PRICES ON CONVENTIONAL BANKS: PENGARUH NILAI TUKAR DAN SUKU BUNGA TERHADAP HARGA SAHAM PADA BANK KONVENSIONAL - Ihwan Satria Lesmana; Listiawati Listiawati; Abdul Bahits (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2022)
One of the benchmarks in investing is the ease of obtaining information about the development of stock prices on the stock exchange. The information obtained is what is needed for investors who will invest, some information can be used as a reference for investing in the capital market including, interest rate inflation, exchange rates, price fluctuations, trading volume, important information on issuers and others.This study aims to determine how the effect of exchange rates and interest rates together on stock prices in conventional banks listed on the IDX for the 2016-2020 period.This research method uses a quantitative approach. Sources of data in this study is secondary data with a population of 42 banking companies and obtained a sample of 9 banks.Data obtained from the Indonesia Stock Exchange (IDX), the exchange rate (X1) against stock prices (Y) in conventional banks t-test calculation results t-test value (0.792 < 2.016) and a significance value of 0.433 > (0.05), interest rates (X2) on stock prices (Y) in conventional banks t-test results of t-test calculations (0.098 < 2.016) and a significance value of 0.923 > (0.05). Partially test (F-Test), together the exchange rate (X1) and interest rates (X2) variables on stock prices (Y) in conventional banks with the results of the calculated value Fcount (0.424) < Ftable (3.220), and it is known significance value of 0.657 > 0.05.The conclusion in this study states that the exchange rate has no effect on stock prices in conventional banks, interest rates have no effect on stock prices in conventional banks, as well as joint testing of exchange rates and interest rates has no effect on stock prices in conventional banks